The Effect of Different Soaking Times of Gambir (Uncaria gambir (Hunter) Roxb.) on the Examination of Ascaris lumbricoides Eggs as an Alternative Stain to Eosin - Tantri Rahmatika; Ari Nuswantoro; Laila Kamilla (Borneo Scientific Publishing, 2025)
Ascaris lumbricoides is a type of helminth that can infect humans. One laboratory method for its examination is the use of 2% eosin staining with the direct slide method. However, eosin poses potential hazards to both the environment and human health, thus prompting the need for an alternative, eco-friendly staining agent. Gambir (Uncaria gambir (Hunter) Roxb.) contains red catechu, which imparts a red coloration to solutions. This study aims to evaluate the staining differences based on varying soaking times of Gambir extract for staining Ascaris lumbricoides eggs as a natural alternative to eosin. This research is a quasi-experimental study using purposive sampling. The Gambir samples were soaked in 96% ethanol for 1 hour, 1 hour 30 minutes, and 2 hours. Each treatment was replicated 9 times, resulting in a total of 27 samples. The staining was conducted using the direct slide method to examine Ascaris lumbricoides eggs. The results showed that Gambir soaked for 1 hour yielded a staining quality of 41.67%, 1 hour 30 minutes resulted in 68.51%, and 2 hours resulted in 87.96%, while the 2% eosin control achieved a staining quality of 100%. Based on the results of this study on the variation in soaking time of gambier (Uncaria gambir (Hunter) Roxb.) as an alternative dye to eosin in the examination of Ascaris lumbricoides eggs, it can be concluded that the staining success rate increases with longer soaking durations.